Current Assets, Current Liabilities and Profitability: A Cross Industry Analysis - Paul, Sujan Chandra; Rahman, Md. Asiqur; Jiasmin, (Journal of Asian Business Strategy, 2021)
This study investigates the relationship between net profit after tax and total assets, total equities, total turnover, current assets and current liabilities. Unbalanced panel Data of 49 Companies from 5 industries listed in Dhaka Stock Exchanges from 2010-2019 were collected from the website of that companies. Ordinary Least Square (OLS), Pooled Ordinary Least Square (POLS), Driscoll-Kraay (DK), Second Stage Least square (2SLS), Generalized Methods of Moments (GMM) models are used in this study. This research found that total assets (TA) had significant positive relationship with net profit after tax (NPAT) in all models except POLS and GMM models, total turnover (TT) had significant positive relationship with net profit after tax in all models and current assets (CA) had significant negative relationship with net profit after tax in OLS and 2SLS model in food and allied sector. In Fuel and power sector, it is found that NPAT and TA had significant negative relationship in all models except GMM. In this sector, TE, TT, CA had significant positive relationship in different models but CL had insignificant relationship. In Pharmaceuticals and Chemical industry and Engineering sector, TE, TT, CA and CL had significant positive relationship in different models but in textile industry there is no significant relationship among these variables though the overall model is significant at 10% level.